2021
DOI: 10.1111/jcpe.13506
|View full text |Cite
|
Sign up to set email alerts
|

Global, regional, and national burden of severe periodontitis, 1990–2019: An analysis of the Global Burden of Disease Study 2019

Abstract: Aim Up‐to‐date epidemiological studies on the global burden of severe periodontitis is scarce. This study aimed to present the latest estimates for prevalence of severe periodontitis from 1990 to 2019, by region, age, and level of socio‐demographic development. Materials and Methods Estimates from the Global Burden of Disease study 2019 were used to investigate burden and trends of prevalence of severe periodontitis and its association with socio‐demographic development at global, regional, and national level.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
161
1
5

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 240 publications
(225 citation statements)
references
References 39 publications
4
161
1
5
Order By: Relevance
“…The treatment of 4-hydroxybenzenecarboximidamide (1) with ethyl chloroacetate in anhydrous conditions produced ethyl-2-(4-carbamimidoylphenoxy)acetate (2) (Scheme 1). In this esterification reaction, the hydrogen from the hydroxyl group underwent replacement with the ethylacetate group of ethyl chloroacetate to form compound (2). Previous research reported that reacting hydroxybenzaldehyde with ethyl chloroacetate leads to the successful synthesis of cyclic esters [21].…”
Section: Chemistrymentioning
confidence: 99%
“…The treatment of 4-hydroxybenzenecarboximidamide (1) with ethyl chloroacetate in anhydrous conditions produced ethyl-2-(4-carbamimidoylphenoxy)acetate (2) (Scheme 1). In this esterification reaction, the hydrogen from the hydroxyl group underwent replacement with the ethylacetate group of ethyl chloroacetate to form compound (2). Previous research reported that reacting hydroxybenzaldehyde with ethyl chloroacetate leads to the successful synthesis of cyclic esters [21].…”
Section: Chemistrymentioning
confidence: 99%
“…Global population growth accounted for 67.9% of the increase in the number of prevalent cases of severe periodontitis in the past 20 years. In 2019, the number of globally prevalent cases of severe periodontitis was 1.1 billion, with this number being higher in less developed countries/regions 6 . Reportedly, there are 500–700 common oral species in different oral structures and tissues, and only approximately 280 of these species have been cultured and formally named.…”
Section: Introductionmentioning
confidence: 99%
“…The agestandardized prevalence rate in 2019 was 13109/100000. From 1990 to 2019, the global age-standardized prevalence rate increased by 8.44% [5]. Periodontitis is also related to systemic diseases, such as cardiovascular disease, rheumatoid arthritis, respiratory disease, resulting in more serious effects on general health [2,[6][7][8].…”
Section: Introductionmentioning
confidence: 99%